ANALISIS PERHITUNGAN PAJAK PENGHASILAN BADAN PADA PT. INDRA MIGAS BERSAMA - Permatasari, Reskia Dwi; Norlena; Hamdani (Universitas Lambung Mangkurat, 2022)
In terms of business turnover/circulation of a 3kg LPG agent, there are two types, namely business turnover/circulation that has been subject to Final Income Tax and business turnover/circulation that is not subject to Final Income Tax. PT. Indra Migas Bersama is a company operating in the oil and gas sector as a supplier or agent for 3 kg LPG gas cylinders in collaboration with PT. Pertamina Patra Niaga. The purpose of this research is to determine the calculation of Corporate Income Tax carried out by PT. Indra Migas Bersama 2020 and to provide Corporate Income Tax calculations in accordance with Law no. 36 of 2008. The method used in this research is descriptive quantitative, the quantitative data obtained by the author is then processed and analyzed to explain the process of calculating corporate income tax at PT. Indra Migas Bersama. From the research results, it shows that PT. Indra Migas Bersama has carried out its tax obligations well, but is still mistaken in calculating its corporate income tax.